Analisis Sistem Distribusi 20 kV Untuk Memperbaiki Kinerja Dan Keandalan Sistem Distribusi Menggunakan Electrical Transient Analisys Program - Abrar Tanjung (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Electric power is the basic human needs in life. In Indonesia, electricity partly served by the State-Owned Company (PLN) and the other using an electric generator engine with its own power as an energy source, such as: the increasing number of industries and companies in the rapidly growing demand PLN electricity supply must be reliable, inexpensive and economical. With the increasing demand for electricity resulted in the development of generation capacity and transmission line / distribution.The distance between plants with consumers so far the distribution of electrical power through a long transmission line is generally in the form of an open airway, causing disturbances on the electrical system the greater the chance of interference. Such defects if left unchecked will lead to substantial fault current and can disrupt electric power distribution to the consumer. Result and analisys In research to improve the performance and reliability of distribution systems by optimizing the determination of optimum mounting location in PT. PLN (Persero) Cabang Dumai Gardu Hubung Ujung Tanjung for the capacitor 3 x 600 kVAr using program ETAP 4.0.0 version accepted in order to obtain a voltage of 17.6 kV irreparable loss and saving power of 553 kW and 817 kVAr.Reliability level of 0.7638 (index value 76%)Keywords: Distribution systems, capacitors, power loss, voltage drop